2020
DOI: 10.1159/000505592
|View full text |Cite
|
Sign up to set email alerts
|

Korean Red Ginseng Inhibits Amyloid-β-Induced Apoptosis and Nucling Expression in Human Neuronal Cells

Abstract: <b><i>Introduction:</i></b> The accumulation of amyloid-β (Aβ) plaque in the brain is a characteristic feature of Alzheimer’s disease (AD) and the cause of fatal oxidative damage to neuronal cells. Korean red ginseng (RG) is used extensively in traditional medicine and is known to have anti-oxidative and anti-inflammatory properties. <b><i>Objective:</i></b> This study aims to investigate whether Korean RG extract inhibits Aβ-induced neuronal apoptosis. <b>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Thus, Aβ 25-35 was chosen for this experiment. The doses of Aβ 25-35 in our study were used according to relevant studies [ 36 , 37 ]. We firstly applied 5, 10, 20 or 50 μmol/L of Aβ 25-35 to test the neurotoxicity of Aβ 25-35 in the PC 12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Aβ 25-35 was chosen for this experiment. The doses of Aβ 25-35 in our study were used according to relevant studies [ 36 , 37 ]. We firstly applied 5, 10, 20 or 50 μmol/L of Aβ 25-35 to test the neurotoxicity of Aβ 25-35 in the PC 12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Korean red ginseng extract (KRG) has been studied as a multi-component drug for AD in the clinical phase II. In vitro experiments, KRG inhibited apoptosis by activating the PI3K/Akt signaling pathway, suppressed NF-κB expression and decreased mitochondrial membrane potential, and also restored mitochondrial respiration associated with ATP production ( Nguyen et al, 2015 ; Shin et al, 2019 ; Choi et al, 2020 ). In addition, in 5XFAD mice that expressed five familial AD mutations, it was further demonstrated that KRG could inhibit the occurrence of mitochondrial dysfunction by protecting the mitochondrial fusion and fission processes, thereby protecting AD mice ( Shin et al, 2019 ).…”
Section: Neuronal Degenerative Diseases and Herbal Medicinementioning
confidence: 98%
“…In this background, ginseng, a widely used traditional medicine for centuries, could be a new alternative in the treatment of AD. Ginseng has been reported to have protective effects via multiple brain pathways, including anti-oxidative, anti-inflammatory, and immunomodulatory properties ( Park et al, 2013 ; Hossen et al, 2017 ), and some preclinical studies have revealed that ginseng has an inhibitory effect on Aβ pathology ( Lee et al, 2001 ; Kim et al, 2013 ; Choi et al, 2017 , 2020 ). Many human studies have also reported non-specific cognitive benefits of ginseng ( Geng et al, 2010 ; Lho et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%